Recent Advances in Reactive Oxygen Species (ROS)-Responsive Polyfunctional Nanosystems 3.0 for the Treatment of Osteoarthritis - Ding DF; Xue Y; Wu XC; Zhu ZH; Ding JY; Song YJ; Xu XL; Xu JG (Journal of Inflammation Research, 2022)
Dao-Fang Ding,1,2,* Yan Xue,3,* Xi-Chen Wu,1,2,* Zhi-Heng Zhu,1,2 Jia-Ying Ding,1,2 Yong-Jia Song,1,2 Xiao-Ling Xu,4 Jian-Guang Xu1,2 1Center of Rehabilitation Medicine, Yueyang Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 2School of Rehabilitation Science, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 3Shanghai Yangzhi Rehabilitation Hospital (Shanghai Sunshine Rehabilitation Centre), Tongji University, Shanghai, People’s Republic of China; 4Shulan International Medical College, Zhejiang Shuren University, Hangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiao-Ling Xu, Shulan International Medical College, Zhejiang Shuren University, 8 Shuren Street, Hangzhou, 310015, People’s Republic of China, Email ziyao1988@zju.edu.cn Jian-Guang Xu, Center of Rehabilitation Medicine, Yueyang Hospital, Shanghai University of Traditional Chinese Medicine, 1200 Cailun Road, Shanghai, 200000, People’s Republic of China, Email xjg@shutcm.edu.cnAbstract: Osteoarthritis (OA) is an inflammatory and degenerative joint disease with severe effects on individuals, society, and the economy that affects millions of elderly people around the world. To date, there are no effective treatments for OA; however, there are some treatments that slow or prevent its progression. Polyfunctional nanosystems have many advantages, such as controlled release, targeted therapy and high loading rate, and have been widely used in OA treatment. Previous mechanistic studies have revealed that inflammation and ROS are interrelated, and a large number of studies have demonstrated that ROS play an important role in different types of OA development. In this review article, we summarize third-generation ROS-sensitive nanomaterials that scavenge excessive ROS from chondrocytes and osteoclasts in vivo. We only focus on polymer-based nanoparticles (NPs) and do not review the effects of drug-loaded or heavy metal NPs. Mounting evidence suggests that polyfunctional nanosystems will be a promising therapeutic strategy in OA therapy due to their unique characteristics of being sensitive to changes in the internal environment.Keywords: polyfunctional nanosystems, osteoarthritis, reactive oxygen species, chondrocytes, osteoclasts